SOCIAL IMPACT OF IMMIGRATION TO THE UNITED STATES - N. E. Petrovskaya (Вестник университета)
This paper discusses the main social impact of immigration to the United States. The article uses systems for a comprehensive review of immigration on the most important American institutions and the integration of immigrants and their children into American society. A comprehensive analysis of the socio-demographic characteristics of immigrants is carried out. Theoretical and methodological analysis of Russian and foreign research, information and statistical materials of the U.S. Census Bureau, as well as materials of American research centers, including Gallup, Pew Research Center. Large-scale immigration has led to changes in the country’s racial and ethnic balance, with long-term changes. The growth of the working-age population in the United States is driven by immigrants and their children. The first time in Gallup’s trend that the percentage wanting increased immigration has exceeded the percentage who want decreased immigration.